If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -7) + 2 = 0 Reorder the terms: -3(-7 + x) + 2 = 0 (-7 * -3 + x * -3) + 2 = 0 (21 + -3x) + 2 = 0 Reorder the terms: 21 + 2 + -3x = 0 Combine like terms: 21 + 2 = 23 23 + -3x = 0 Solving 23 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -3x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -3x = 0 + -23 -3x = 0 + -23 Combine like terms: 0 + -23 = -23 -3x = -23 Divide each side by '-3'. x = 7.666666667 Simplifying x = 7.666666667
| 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 | | 5m=10-5m | | 3(x+15)+4(9-x)=0 | | 8r=-4r-12 | | x^2-6=55 | | 0.2x+9=8(0.4x-1) | | -2=3n+6-5n | | 244.92=2r*3.14 | | -3+2x=3x-4 | | 9(3x-1)-5=6x | | 8x-5=-2x+1 | | 2+3x=6+4x | | -.01t^2+.7t-10=0 | | 8x-5=-2x+11 | | 6(y-2)=-36 |